Magnetic monopole and CP symmetry violation at finite temperature - Sitenko, Yu.A.; Solovyov, A.V.; Vlasii, N.D. (Вопросы атомной науки и техники, 2007)
An ideal gas of relativistic massive electrons in the background of a Dirac magnetic monopole is considered. We find that in the case of CP symmetry violation this system acquires, in addition to charge, also squared orbital angular momentum, squared spin, and squared total angular momentum. The functional dependence of these quantities on the temperature and the CP-violating vacuum angle is determined. Thermal quadratic fluctuations of conserved quantities are examined, and we analyze, when charge and squared total angular momentum become sharp quantum observables rather than mere expected averages of many quantum measurements. Розглядається ідеальний газ релятивістських масивних електронів у присутності магнітного монополя Дірака. Знайдено, що при порушенні CP-симетрії в цій системі поряд із зарядом виникають також квадрат орбітального кутового моменту, квадрат спіну та квадрат повного кутового моменту. Визначена функціональна залежність цих величин від температури та вакуумного кута, що порушує CP-симетрію. Досліджені температурні квадратичні флуктуації величин, що зберігаються, і з’ясовано, коли заряд та квадрат повного кутового моменту стають точними квантовими спостережуваними, а не просто очікуваними середніми по багатьом квантовим вимірюванням. Рассматривается идеальный газ релятивистских массивных электронов в присутствии магнитного монополя Дирака. Обнаружено, что при нарушении CP-симметрии в этой системе наряду с зарядом возникают также квадрат орбитального углового момента, квадрат спина и квадрат полного углового момента. Определена функциональная зависимость этих величин от температуры и вакуумного угла, нарушающего CP-симметрию. Исследованы температурные квадратичные флуктуации сохраняющихся величин, и установлено, когда заряд и квадрат полного углового момента становятся точными квантовыми наблюдаемыми, а не просто ожидаемыми средними по многим квантовым измерениям.